2020
DOI: 10.1101/2020.04.21.20068858
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 serological analysis of COVID-19 hospitalized patients, pauci-symptomatic individuals and blood donors

Abstract: It is of paramount importance to evaluate the prevalence of both asymptomatic and symptomatic cases of SARS-CoV-2 infection and their antibody response profile. Here, we performed a pilot study to assess the levels of anti-SARS-CoV-2 antibodies in samples taken from 491 preepidemic individuals, 51 patients from Hôpital Bichat (Paris), 209 pauci-symptomatic individuals in the French Oise region and 200 contemporary Oise blood donors. Two in-house ELISA assays, that recognize the full-length nucleoprotein (N) or… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
94
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(111 citation statements)
references
References 35 publications
(66 reference statements)
11
94
0
6
Order By: Relevance
“…The flow cytometry-based method we employed demonstrated the highest degree of specificity and sensitivity. A similar method was also recently used in an independent study, reaching comparable results, except no cross-reactivity with HCoV was suggested 9 . Although not specifically investigated in the latter study, detection of cross-reactivity with HCoV was deliberately avoided by higher dilution of serum samples.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The flow cytometry-based method we employed demonstrated the highest degree of specificity and sensitivity. A similar method was also recently used in an independent study, reaching comparable results, except no cross-reactivity with HCoV was suggested 9 . Although not specifically investigated in the latter study, detection of cross-reactivity with HCoV was deliberately avoided by higher dilution of serum samples.…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, infection with SARS-CoV-2 has recently been shown to increase IgG seroreactivity to HCoVs 21 , supporting the existence of shared epitopes. Numerous serology assays that are being developed have also detected SARS-CoV-2reactive antibodies in a considerable proportion of SARS-CoV-2-uninfected individuals, which has often been considered as unspecific binding, rather than HCoV-elicited specific antibodies [9][10][11][12][13][14][15][16][17][18][19][20]22 . Based on our data, we would argue that this is the result of cross-reactivity between HCoVs.…”
mentioning
confidence: 99%
“…There are a large number of immunological assays capable of measuring the antibody response to SARS-CoV-2 including neutrilization assays, ELISA, Luminex, Luciferase Immunoprecipitation System (LIPS), peptide microarrays and more [34].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, hACE2 was PCR amplified adding SpeI, XhoI, and attB sites using forward primer (5'-TCC CTC ACT AGT ACA AGT TTG TAC AAA AAA GCA GGC TGC CAC CAT GTC AAG CTC TTC CTG GCT C -3') and reverse primer (5'-AAA AAA CTC GAG ACC ACT TTG TAC AAG AAA GCT GGG TTT AAG CGG GCG CCA CCT -3') and cloned into pLenti6-H2B-mCherry using XhoI and SpeI sites. phCMV-SARS-CoV2-S was previously described 55 . pLV-EF1α-TMPRSS2-IRES-Hygro was generated by gateway cloning of pCSDest-TMPRSS2 into pLV-EF1α-IRES-Hygro-DEST.…”
Section: Methodsmentioning
confidence: 99%